Analysis of factors affecting customer satisfaction (PT Bank Mandiri (Persero) TBK Padang Belakang Olo Branch) - Henderson, Novreza; Heryanto, (Technium Social Sciences Journal, 2020)
Basically the goal of a business is to create customers who are satisfied. The creation of satisfaction can provide several benefits, including the relationship between the company's customers are harmonious, provide a good foundation for the purchase and creation of customer loyalty and establish a recommendation by word of mouth (word-ofmouth) which is advantageous for the customer, This research conducted in PT Bank Mandiri (Persero) TBK Padang Belakang Olo Branch sample of 100 customers with sample selection. In this study usingstratified random sampling technique, Bysampling in certain strata then taken at random with equal proportion according to the position in the population, With the data were analyzed by using multiple linear regression analysis. Servqual significantly affect customer satisfaction and positive experience for the customer PT Bank Mandiri (Persero) TBK Padang Belakang Olo Branch, customer value as wellsignificantly affect customer satisfaction and positive experience for the customer PT Bank Mandiri ( Persero) TBK Padang Belakang Olo Branch. Product quality can not beaffects customer satisfaction PT Bank Mandiri (Persero) TBK Padang Belakang Olo Branch. Emotionalcan not affectcustomersatisfactionforcustomers PT Bank Mandiri (Persero) TBK Padang Belakang Olo Branch . Prices are not able to affect customer satisfaction for customers Bank PT Bank Mandiri (Persero) TBK Padang Belakang Olo Branch. Cost significantly affect customer satisfaction and positive experience for the customer PT Bank Mandiri ( Persero) TBK Padang Belakang Olo Branch.It can be concluded that the higher Servqua and, customers value a customer satisfaction will also increase, in addition to lower customers' costs incurred in obtaining products and services PT Bank Mandiri (Persero) TBK Padang Belakang Olo Branch, then customer satisfaction will increase.